Learning Core Leadership: Seeing the Problem We Do Not See. Issue 7 (31st October 2019) - Edwards, Calvin; Woo, Jason
ABSTRACT: Uniformed health care professionals operate in complex environments. We presume our partners' mission perspective mirrors our own; they share and support our goals. This case demonstrates how this "self-deception" blinds and limits us. Seeing this self-deceit enables us to adjust our efforts to better accomplish our mission.